Comparative Efficacy and tolerability of Lasoride and Spiromide in congestive Cardiac Failure - Hafizullah, Muhammad; Bangash, Kamran; Abbas, Farhat (Journal of Postgraduate Medical Institute, 2011)
Diuretics play primary role in fluid over loaded patients with CCF. Combination of potassium sparing agents with loop diuretics enhance the diuretic effect, conserve potassium and reduce the number of tablet. This study was carried out to see the efficacy safety and tolerability of lasoride against spiromide. This was a short term, randomised signle blind study. Patients were assessed for clinical hemodynamic and biochemical changes. Patients were well matched regarding age, sex, weight, hemodynamic and biochemical status. both the drugs improved clinical signs and symptoms without much effect on biochemical status. Gastrointestinal side effects were more common in spiromide group (42%) Vs 5%) and Gynaecomastic was more frequent in spiromide group (25% Vs 2.5%) in lasoride (p<0.05). Both lasoride and spiromide were effective and safe; lasoride was better in tolerability.